1996
DOI: 10.1093/infdis/174.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Group C Rotavirus in Infants with Extrahepatic Biliary Atresia

Abstract: The purpose of this retrospective study was to examine liver tissue from patients with cholestatic disease for the presence of group C rotavirus RNA. The reverse transcriptase-polymerase chain reaction (PCR) for genes 5 and 6 was used, and the PCR products were subjected to liquid hybridization with a 32P-labeled probe. A second amplification with nested primers was also used. Samples from 32 subjects (20 with biliary atresia or choledochal cyst and 12 controls) were tested. Ten of 20 biliary atresia patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
176
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(181 citation statements)
references
References 36 publications
3
176
1
1
Order By: Relevance
“…Because rotavirus has been found in the blood of infected infants, it is possible that a perinatal rotavirus inoculation could result in biliary epithelial injury in a young infant. Detection of rotavirus within the livers of children affected with biliary atresia has been reported but not in a consistent fashion (4,27). Further study will be necessary to determine whether rotavirus has a causal effect in the disease process that occurs in humans.…”
Section: Vol 81 2007mentioning
confidence: 99%
See 1 more Smart Citation
“…Because rotavirus has been found in the blood of infected infants, it is possible that a perinatal rotavirus inoculation could result in biliary epithelial injury in a young infant. Detection of rotavirus within the livers of children affected with biliary atresia has been reported but not in a consistent fashion (4,27). Further study will be necessary to determine whether rotavirus has a causal effect in the disease process that occurs in humans.…”
Section: Vol 81 2007mentioning
confidence: 99%
“…Two types of evidence support a viral role in the pathogenesis of biliary atresia. The first type is patient-based studies in which viruses, including reovirus (11,19,20), cytomegalovirus (7,9), human papillomavirus (8), Epstein-Barr virus (10), and rotavirus (27), were found in the livers of infants with biliary atresia. The second type of evidence is the murine model of inflammatory cholangiopathy in which newborn mice injected with rhesus rotavirus (RRV) develop extrahepatic biliary obstruction and death (28).…”
mentioning
confidence: 99%
“…A wide range of enteric viruses has been implicated including REOvirus and cytomegalovirus (CMV) but clinical evidence of exposure and its relevance is conflicting whether derived from serological studies (7,8,9) or more directly from PCR studies on liver biopsies to detect viral nucleic acids (10).…”
Section: Introductionmentioning
confidence: 99%
“…Two viruses which have been studied in humans as potential causes of duct damage are reovirus and rotavirus. Tyler et al [7] reported finding nested RT-PCR evidence of reovirus in infants with BA and Riepenhoff-Talty et al [8] found RT-PCR evidence of group C rotavirus (Reovirdae family) in BA hepatobiliary tissue. However, other investigators failed to find presence of these viruses in BA patients [9,10].…”
Section: Introductionmentioning
confidence: 99%